The Role of Emotional Intelligence in Predicting Peer Relationships in Adolescents - Bahar Güler; Serhat Turan (Journal of Educational Issues, 2024)
The aim of the research is to determine how much peer relationships are explained by emotional intelligence in adolescents. For this purpose, 539 (283 female+256 male) adolescent individuals participated in the study. “Personal Information Form”, “Trait Emotional Intelligence—Adolescent Questionnaire Short Form (TEIQue-ASF)” and “Friendship Qualities Scale” were used as data collection tools in the research. The data collected online were coded and transferred to the SPSS program, and descriptive statistics, Pearson correlation and Regression techniques were used in statistical analysis. In the study, the level of significance was taken as p < .001. According to the results of the analysis, it was determined that there was a positive, significant and low-level correlation between emotional intelligence and peer relationships (r = .283, p = .000). As a result of the regression analysis, in Model 1, TEIQue-ASF explained 7.8% of the total variance of Friendship Qualities; In Model 2, on the other hand, TEIQue-ASF explained 12.7% of the total variance regarding Friendship Qualities, the variables of gender and playing in the school team. As a result, it can be said that emotional intelligence is an important factor for peer relationships in adolescents.